Biophysical and Biochemical Outcomes of Chlamydia pneumoniae Infection Promotes Pro-atherogenic Matrix Microenvironment - Evani, Shankar J.; Dallo, Shatha F.; Ramasubramanian, Anand K. (Frontiers in Microbiology, 2016)
Multiple studies support the hypothesis that infectious agents may be involved in the pathogenesis of atherosclerosis. Chlamydia pneumoniae is strongly implicated in atherosclerosis, but the precise role has been underestimated and poorly understood due to the complexity of the disease process. In this work, we test the hypothesis that C. pneumoniae-infected macrophages lodged in the subendothelial matrix contribute to atherogenesis through pro-inflammatory factors and by cell-matrix interactions. To test this hypothesis, we used a 3D infection model with freshly isolated PBMC infected with live C. pneumoniae and chlamydial antigens encapsulated in a collagen matrix, and analyzed the inflammatory responses over 7 days. We observed that infection significantly upregulates the secretion of cytokines TNF-, IL-1, IL-8, MCP-1, MMP, oxidative stress, transendothelial permeability, and LDL uptake. We also observed that infected macrophages form clusters, and substantially modify the microstructure and mechanical properties of the extracellular matrix to an atherogenic phenotype. Together, our data demonstrates that C. pneumoniae-infection drives a low-grade, sustained inflammation that may predispose in the transformation to atherosclerotic foci.